First experience of vectorizing electromagnetic physics models for detector simulation. Issue 9 (December 2015) - Amadio, G; Apostolakis, J; Bandieramonte, M; Bianchini, C; Bitzes, G; Brun, R; Canal, P; Carminati, F; Licht, J de Fine; Duhem, L; Elvira, D; Gheata, A; et al.
Abstract: The recent emergence of hardware architectures characterized by many-core or accelerated processors has opened new opportunities for concurrent programming models taking advantage of both SIMD and SIMT architectures. The GeantV vector prototype for detector simulations has been designed to exploit both the vector capability of mainstream CPUs and multi-threading capabilities of coprocessors including NVidia GPUs and Intel Xeon Phi. The characteristics of these architectures are very different in terms of the vectorization depth, parallelization needed to achieve optimal performance or memory access latency and speed. An additional challenge is to avoid the code duplication often inherent to supporting heterogeneous platforms. In this paper we present the first experience of vectorizing electromagnetic physics models developed for the GeantV project.